2010
DOI: 10.1016/j.electacta.2010.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Lithium intercalation into amorphous FePO4 cathode in aqueous solutions

Abstract: Minakshi, M. (2010) Lithium intercalation into amorphousThis is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 25 publications
(16 reference statements)
1
34
0
Order By: Relevance
“…The standard reference electrode was Hg/HgO purchased from Koslow Scientific. The cell design and its experimental procedures for the galvanostatic and slow scan cyclic voltammetric studies were made in a similar way to that described in our earlier report [15]. galvanostatically at a constant current of 0.2 mA (on mass density 8 mA/g) using an 8 channel battery analyzer from MTI Corp., USA, operated by a battery testing system (BTS).…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…The standard reference electrode was Hg/HgO purchased from Koslow Scientific. The cell design and its experimental procedures for the galvanostatic and slow scan cyclic voltammetric studies were made in a similar way to that described in our earlier report [15]. galvanostatically at a constant current of 0.2 mA (on mass density 8 mA/g) using an 8 channel battery analyzer from MTI Corp., USA, operated by a battery testing system (BTS).…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…Hg/HgO purchased from Koslow Scientific served as the standard reference electrode. The cell design and its experimental procedures for the galvanostatic and slow scan cyclic voltammetric studies were made in a similar way to that described in our earlier report [21]. galvanostatic experiments, the cell was discharged/ charged galvanostatically using an 8 channel battery analyzer from MTI Corp., USA, operated by a battery testing system (BTS).…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…The experimental procedures for the slow scan cyclic voltammetric studies were similar to those reported earlier [23]. We fabricated the LiNiPO 4 cathode for electrochemical charge-discharge test with the following procedure; a pellet was M a n u s c r i p t 6…”
Section: Introductionmentioning
confidence: 99%